Cloning and molecular modeling of free fatty acid receptor GPCR 43 with dietary flavonoids as novel ligands: DOI: 10.48129/kjs.19029 - Ihtsham, Arooma; Hayat, Rida; Khan, Fariha (Kuwait Journal of Science, 2022)
G-protein couple receptors (GPCRs) are considered as the largest membrane protein family involved in the regulation of body homeostasis in health and disease. GPCR43 or FFA2 (free fatty acid receptor 2) is implicated in diabetes. Efficient methods are needed to express GPCRs for structural studies. Small GPCR fragments consisting of 1-2 transmembrane domains are routinely used in NMR studies. In the present study, the first three transmembrane segments 1-3 of GPCR43 (GPCR43-TM1-3) were cloned and expressed with expression enhancement tag, AT4 and His tag at the C and N termini respectively into pET23b(+). The plant compounds, flavonoids, with reported beneficial effects in diabetes mellitus type 2 (T2DM) were subjected to docking against the target, GPCR43. Our results revealed that the ligands exhibited better binding interaction to GPCR43. Diosmin was predicted to be the best ligand with good binding affinity than the other ligands. Hence, we concluded that Diosmin may become a potential drug candidate for T2DM via GPCR43 pathway. However, studies are warranted to confirm its efficacy in animal models of T2DM.